Highway Capacity Estimation: International Regulation and Neurostructural Remodeling Approach - Sysoev, Anton; Anikienko, Tatyana; Blyumin, Semen (Periodica Polytechnica Transportation Engineering, 2020)
Increasing number of personal vehicles and cargo transportation requires the development of a well-planned transport policy within states and states associations. The existing normative acts give different directions in the field of regulation of transportation processes. One of the most important aspects in assessing the existing state transport arteries and planning new ones is the analysis of their capacity, which could be performed in various ways. The classical approach defines capacity as a certain value that is constant for the entire period under consideration. However, this value is changing at any given point in time depending on various factors (weather, psychological, accidental), and this fact determines the stochastic nature of this indicator. The paper presents an overview of existing approaches and a perspective approach that defines capacity as a random variable. The paper also presents the method to model highway capacity, which delivers greater accuracy compared to traditional approaches used in Russia and Germany. Using the proposed approach it is possible to obtain adequate values of highway capacity, which is important in assessing the quality of the functioning of existing highways and planning new ones.